2017
DOI: 10.1016/j.socscimed.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Two approaches, one problem: Cultural constructions of type II diabetes in an indigenous community in Yucatán, Mexico

Abstract: The emerging epidemic of obesity and type II diabetes in Mexico has recently propelled the nation into the public health spotlight. In the state of Yucatán, the experience of diabetes is greatly impacted by two cultural constructions of disease. In this setting, elements of Yucatec Mayan health practices as well as the biomedical model affect the approach to type II diabetes. Both frameworks offer unique understandings of the etiology of diabetes and recommend different ways to manage the condition. Based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Some authors also note how the adoption of lifestyle changes recommended by medical staff, in particular diet, interacts with gender. For instance, similar to our data, these authors found that women with diabetes face greater barriers to diet change given their workload because of gender norms (12) .…”
Section: The Importance Of Culture In Health Behaviourssupporting
confidence: 89%
See 3 more Smart Citations
“…Some authors also note how the adoption of lifestyle changes recommended by medical staff, in particular diet, interacts with gender. For instance, similar to our data, these authors found that women with diabetes face greater barriers to diet change given their workload because of gender norms (12) .…”
Section: The Importance Of Culture In Health Behaviourssupporting
confidence: 89%
“…This research also shows how poverty, cultural marginalization, and the processed food and sugary beverage industries converge in complex ways to contribute to the development of diabetes among indigenous peoples, including Mexican Mayans, and to create multiple barriers to the adoption of doctor-recommended dietary changes (12) . Page-Pliego specifically investigates the increased consumption of sugary beverages in culturally marginalized groups living in poverty, such as many Mexican Mayans, and its ties with taste but also with political and socio-economic processes that lead to easy availability of these drinks and make them socially desirable (13,48) .…”
Section: The Importance Of Culture In Health Behavioursmentioning
confidence: 84%
See 2 more Smart Citations
“…Even when health services are covered by public insurance, individuals may be required to pay for extra services. Culturally constructed perceptions of T2DM causes and treatments, such as the relationship between stress and disease, may affect individual understanding of proper diabetes management (Frank & Durden, 2017). In addition, increased availability and lower cost of calorie-dense products in the Yucatan have led to greater consumption of foods that contribute to obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%